Menimbang Kembali Alternatif Mekanisme Pemilihan Kepala Daerah di Indonesia - Muhadam Labolo (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2016)
Direct local election has begun since 2004 and has regulated in Law No. 32 Year 2004 about Local Government. Direct local election is giving several advantages namely local head who elected by the people knows about people need. Beside that, direct control of people could border their local head to do something out of their want. In other side, there are many troubles of direct local election in implementation process like there are no mechanism for people to insist local head’s promise to them. So that, several academicians and practioners suggest back to the indirect election like a decade ago. This paper try to give academic personal perspective and consideration that local election can adopt indirect local election again.